The People's Bank of China and its monetary policy - Cao Tinggui (Fachhochschule für Wirtschaft Berlin, Business Institute Berlin, 2001)
Since 1984, the People's Bank of China has started to function as a central bank. In October 1998, the People's Bank of China carried out significant reform in the management system, abolishing the 31 provincial branches and establishing the 9 regional branches, in order for the People's Bank of China to strengthen the authority and independence in the execution of the monetary policy. Fundamentally speaking, a central bank's independence is given by the nature of the market economy. China is in the process of transforming itself from the old economic system to the new one, especially the reform of the state-owned enterprises has not been finished yet, therefore the economic foundation for the independence of the central bank in the execution of the monetary policy is under construction.
Keywords: 330